The influence of oral and topical channa striatus on tensile strength, epitheliazation, fibroblast count and hydroxyproline assay in laparotomy wound healing of malnourished rats - Husin , Rezqa (2011)
Introduction: Channa striatus has been used in traditional medicine for centuries to accelerate wound healing. Recently several scientific studies have shown the healing properties of Channa striatus. However study yet to be done on its healing effect on laparotomy wound healing which has greater morbidity and mortality in the event of laparotomy wound failure. There is also no study on its healing effect in malnourished patient whom may benefit the most. Objective: The aim of the study is to evaluate the effect of Channa striatus on tensile strength, epitheliazation, fibroblast count, and hydroxyprolene level in the healing of laparotomy wound in malnourished rat. xi Methods: 40 malnourished wistar rat underwent laparotomy and the wound closed primarily. The rats were divided into two groups by block randomization. Group 1 is the control group. Group 2 received oral and topical Channa striatus daily. The rats were euthanized and full thickness strips of the wound were subjected to tensile strength measurement, histopathological examination for epitheliazation and fibroblast counts. Hydroxyprolene assays was not done due to technical problem. Results: The results demonstrates that the group treated with oral and topical channa striatus were significantly higher in tensile strength, epithelial and fibroblast cell counts (p value < 0.001). Conclusion: This study suggests that oral and topical Channa striatus enhances laparotomy wound healing in malnourished rat by increasing the tensile strength, epithelialisation and fibroblast count.